Earnings inequalities and educational mobility in Brazil over two decades - Denis Cogneau; Jérémie Gignoux (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This paper studies the impact of changes in educational opportunities on various definitions of labour market inequalities in Brazil over two decades (1976-96). Using four editions of the nationally representative PNAD survey, we analyze the evolution of overall inequalities and inequalities of opportunity in 40-49 year old males' earnings. We design and implement semiparametric decompositions of the respective effects of (i) schooling expansion, (ii) changes in the structure of earnings, and (iii) changes in intergenerational educational mobility. Earnings inequalities varied little over the period, with a peak in the late 1980s that can be imputed to hyperinflation. First of all, the decompositions show that changes in the distribution of education contributed to the increase in both overall earnings inequalities and inequalities of opportunity among the oldest generations, before sharply reducing them among the post-WWII cohorts. Secondly, the decrease in returns to education also contributed to equalizing labour market opportunities in the 1988-96 period. Thirdly and lastly, the changes in educational mobility were not large enough to significantly affect earnings inequalities, whereas it is shown that they should play a prominent role in equalizing opportunities in the future.
Keywords: D32; D63; J62; O15; 330